ANALISIS TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN METODE RGEC (RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNINGS, CAPITAL) PADA BNI SYARIAH TAHUN 2014-2017 - Nurwijayanti, Maya; Santoso, Lukman (IAIN Ponorogo, 2018)
Abstract: Islamic banks with profit sharing systems have been designed to establish cooperation in bearing business risks and profit sharing between business owners (Shahibul Maal) and fund managers (mudarib). The bank under study is BNI Syariah. This study aims: 1) Knowing how the rating of Bank BNI Syariah's health level is reviewed from the Risk Profile in 2014-2017? 2) Knowing how to assess the soundness of Bank BNI Syariah in terms of Good Corporate Governance in 2014-2017? 3) Knowing how the rating of Bank BNI Syariah's health level is reviewed from Earnings in 2014-2017? 4) Knowing how the soundness rating of Bank BNI Syariah is reviewed from Capital in 2014-2017? This study uses a quantitative descriptive approach, the data collection techniques used are documentation techniques. The method of data analysis uses the RGEC method. The data is taken from the published annual financial reports at BNI Syariah. The analysis results obtained by the Risk Profile Level on BNI Syariah in 2014-2017 are